2014
DOI: 10.1063/1.4896970
|View full text |Cite
|
Sign up to set email alerts
|

Trap-assisted tunneling in InGaN/GaN single-quantum-well light-emitting diodes

Abstract: Based on numerical simulation and comparison with measured current characteristics, we show that the current in InGaN/GaN single-quantum-well light-emitting diodes at low forward bias can be accurately described by a standard trap-assisted tunneling model. The qualitative and quantitative differences in the current characteristics of devices with different emission wavelengths are demonstrated to be correlated in a physically consistent way with the tunneling model parameters

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 21 publications
6
46
1
1
Order By: Relevance
“…In the range of the forward bias at which tunneling occurred, SRH nonradiative recombination was the dominant process in the LED operation. The result was consistent with the reports on trap-assisted tunneling, which employed SRH recombination in the models [17][18][19]. As the DSDRs have a high density of nonradiative recombination defects, which affect the chip operation, the adoption of the PL imaging technique to detect DSDRs can provide an effective inspection and a quick evaluation of LED epi-wafers, allowing the estimation of the properties of the LED chips fabricated from the epi-wafers.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…In the range of the forward bias at which tunneling occurred, SRH nonradiative recombination was the dominant process in the LED operation. The result was consistent with the reports on trap-assisted tunneling, which employed SRH recombination in the models [17][18][19]. As the DSDRs have a high density of nonradiative recombination defects, which affect the chip operation, the adoption of the PL imaging technique to detect DSDRs can provide an effective inspection and a quick evaluation of LED epi-wafers, allowing the estimation of the properties of the LED chips fabricated from the epi-wafers.…”
Section: Discussionsupporting
confidence: 76%
“…Their result suggested that a high dislocation density could be the reason for the high ideality factors. Recently, forward leakage at low and intermediate bias region has been explained considering trap-assisted tunneling [13,[17][18][19]. The results in this work indicate that the DSDRs in LED-4 are regions of high density of dislocations and deep traps, which cause the forward leakage.…”
Section: I-v Characteristics Of Led Chips With Dsdrsmentioning
confidence: 74%
See 3 more Smart Citations